Effects of Biofertilizer Application and Organic Matter Incubation on Soil Chemical Properties - Aisyah; Paranita Asnur; Fitrianingsih; Risnawati (Postgraduate, University of Mataram, 2025)
Soil organic matter is essential for maintaining soil fertility and supporting sustainable agricultural production. However, raw organic matter does not directly enhance soil chemical properties without a sufficient decomposition period. This study evaluated the effects of organic matter incubation and biofertilizer concentrations on soil chemical characteristics. The experiment was conducted from June to August 2024 in the Greenhouse Laboratory of Gunadarma Technopark University, Jamali Village, West Java, using a completely randomized factorial design. Treatments consisted of four biofertilizer concentrations (0, 10, 15, and 20 mL/L) and five incubation periods of cow manure (0, 1, 2, 3, and 4 weeks), each replicated four times, resulting in 80 experimental units. The results showed a significant interaction between incubation duration and biofertilizer concentration on soil pH, organic carbon, total nitrogen, C/N ratio, available phosphorus (P₂O₅), and available potassium (K₂O). The four-week incubation combined with 10–20 mL/L of biofertilizer produced the most notable improvements, increasing pH to neutral levels, raising organic carbon and nitrogen contents, achieving an optimal C/N ratio, and enhancing P availability, although K remained low. These findings indicate that combining biofertilizer application with an adequate incubation period effectively improves soil fertility and offers a viable strategy for long-term soil management and agricultural productivity.